Analisis Pertumbuhan Penjualan, Ukuran Perusahaan, Return On Asset dan Struktur Modal terhadap Nilai Perusahaan (Studi pada Industri Makanan dan Minuman yang Terdaftar Di BEI Periode 2016-2018) - Een Suraiyati; Vinus Maulina; Riril Mardiana Firdaus (Jurnal Riset Mahasiswa Manajemen, 2019)
The purpose of this research is to find out whether there is an influence of sales growth variables, firm size, return on asset and capital structure partially on firm value. This type of research is quantitative research and uses purposive sampling method in determining samples with several predetermined criteria and samples obtained by 13 companies from 18 food and beverage industry companies listed on the Indonesia Stock Exchange for the period of 2016-2018. The analytical method used in testing the research hypothesis is multiple linear regression analysis. The results showed that the variable of sales growth had no effect on firm value, firm size had no effect on firm value, return on asset had an effect on firm value and capital structure had influence on firm value.